2008
DOI: 10.1152/ajpendo.00583.2007
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones and the renal and hormonal response to water immersion-induced volume expansion in type 2 diabetes mellitus

Abstract: Thiazolidinediones cause sodium retention and edema by a direct effect on the kidneys. The aim of this study was to use the technique of head-out water immersion to investigate the effects of rosiglitazone on sodium and volume homeostasis in subjects with type 2 diabetes mellitus. The volume expansion response to water immersion was compared with the response on a non-immersion control day in 12 nondiabetic male subjects and 8 diet-controlled male type 2 diabetic subjects with hourly blood and urine sampling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(40 reference statements)
2
4
1
1
Order By: Relevance
“…Our data seem to be in contrast with results found in a recent publication [35] showing that in type 2 diabetic subjects the impairment of ANP response to immersion was restored by rosiglitazone (after they had taken 4 mg of rosiglitazone every morning for 7 days prior to the study). However, the different type of TZD and the particular stimulus to cause volume expansion head-out water immersion) could explain the differences found in that study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data seem to be in contrast with results found in a recent publication [35] showing that in type 2 diabetic subjects the impairment of ANP response to immersion was restored by rosiglitazone (after they had taken 4 mg of rosiglitazone every morning for 7 days prior to the study). However, the different type of TZD and the particular stimulus to cause volume expansion head-out water immersion) could explain the differences found in that study.…”
Section: Discussioncontrasting
confidence: 99%
“…Exercise training has been shown to decrease sympathetic and increase vagal nervous activity, and improve baroreceptor reflex sensitivity after exercise training [13]. These effects could result in decreased concentrations of renin, angiotensin II, aldosterone, reduction in renal sympathetic outflow, and increase in nitric oxide and atrial natriuretic peptide release, which have been observed previously in healthy individuals and in patients with heart failure [13,16,19]. These effects could result in decreased concentrations of renin, angiotensin II, aldosterone, reduction in renal sympathetic outflow, and increase in nitric oxide and atrial natriuretic peptide release, which have been observed previously in healthy individuals and in patients with heart failure [13,16,19].…”
Section: Resultsmentioning
confidence: 79%
“…Additional effects attributed to exercise being performed specifically in heated water are arterial vasodilatation and reduction in volemia [14,16]. However, changes in neurohormonal secretion, peripheral resistance, and diuresis reported as the result of heated water-based exercise were not associated with reduction in BP in healthy individuals and patients with heart failure [13,14,19]. However, changes in neurohormonal secretion, peripheral resistance, and diuresis reported as the result of heated water-based exercise were not associated with reduction in BP in healthy individuals and patients with heart failure [13,14,19].…”
Section: Resultsmentioning
confidence: 99%
“…This makes them a potential future therapeutic option in patients with type 2 diabetes who are overweight or obese. Subjects with type 2 diabetes have been shown to have a higher exchangeable body sodium, and this propensity to retain sodium may contribute to the pathophysiology of the high prevalence of hypertension in diabetes 42. Therefore, one can argue that potentially the urinary sodium loss resulting from inhibition of SGLT‐2 and the osmotic diuretic effect caused by glycosuria produced by these drugs, may have some advantages in patients with type 2 diabetes, particularly in those who also have hypertension.…”
Section: Potential Clinical Utility Of Sglt‐2 Inhibitorsmentioning
confidence: 99%